Analysis of sound transmission loss in an infinite duct with three dierent finite linings - TİRYAKİOĞLU, BURHAN (My University, 2023)
The study rigorously investigates the propagation of sound waves from an infinite duct lined with three di®erent finite acoustically absorbing materials. Due to multiple discontinuity points, the mode matching method e®ectively solved the problem. The mathematical equations involved are highly complex due to three distinct and finite linings. To overcome this, a numerical solution is obtained, and the e®ects of the geometry\"s parameters on the transmission loss are thoroughly examined. As the length of the finite acoustic absorbing lining increases, the transmission loss decreases. In addition, the graphs clearly illustrate the substantial in°uence that the choice of absorbing lining can have on transmission loss. These findings hold great relevance for absorber systems, highlighting the importance of careful selection in order to achieve optimal performance. The obtained results are compared with another study, and complete agreement is observed, indicating the study\"s accuracy and reliability.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Temel Bilimler (SCI); FİZİK, YOĞUN MADDE; FİZİK, UYGULAMALI; Natural Sciences (SCI); PHYSICS; PHYSICS, CONDENSED MATTER; PHYSICS, APPLIED; İstatistiksel ve Doğrusal Olmayan Fizik; Fizik Bilimleri; Yoğun Madde Fiziği; Statistical and Nonlinear Physics; Physical Sciences; Condensed Matter Physics; finite lining; mode-matching technique; Transmission loss analysis